What is the role of educational games? - Vlasenko, Ludmila; Sulima, Irina (My University, 2012)
This article reveals the basic features of teaching educational games; educational games are analyzed and attention is concentrated on the importance of their development in the teaching of students.
Keywords: навчальна гра; обучающая игра; educational game; мовленнєва діяльність; комунікативна компетентність; речевая деятельность; коммуникативная компетентность; communicative activity; communicative competence; кафедра ділової іноземної мови та міжнародної комунікації